Effects of the Diacylglycerol Complexing Agent, Cremophor, on Nerve-Conduction Velocity and Perfusion in Diabetic Rats - Jack, Alison M; Cameron, Norman E; Cotter, Mary A (Journal of diabetes and its complications, 1999)
The contribution of diacylglycerol (DAG) and protein kinase C (PKC) to diabetic complications has been the subject of debate. In vascular tissues, diabetes increases DAG content, which activates PKC and causes abnormal tissue perfusion. Reduced nerve blood flow has been implicated in the development of neuropathy. However, nerve DAG/PKC activity is not increased and may even be reduced by diabetes, which has also been implicated in neuropathy. The aim was to test whether 2 weeks of treatment with cremophor, an agent that complexes DAG and prevents PKC activation, could correct nerve-conduction velocity (NCV) deficits in rats with 6 weeks of untreated diabetes, as predicted on a vascular hypothesis, or whether this worsened the deficits, as predicted for a direct effect on nerve fibers. Diabetes caused 17.9 ± 0.9% (± SEM) and 15.5 ± 1.6% reductions in sciatic motor and saphenous sensory NCV, respectively, that were largely (79.6 ± 6.3% and 57.8 ± 11.5%) corrected by 100 mg · kg −1 · day −1 cremophor treatment. The effects of cremophor on motor and sensory NCV were completely attenuated by co-treatment with the nitric oxide synthase inhibitor, N G-nitro- l -arginine. In contrast, co-treatment with the cyclooxygenase inhibitor, flurbiprofen, had no effect on NCV. Sciatic nutritive and total endoneurial perfusion were 49.7 ± 3.4% and 51.8 ± 4.2% reduced by diabetes, respectively, and these deficits were 69.5 ± 7.4% and 79.0 ± 11.6% corrected by cremophor treatment. Thus the data suggest that an increased DAG/PKC vascular mechanism, perhaps linked to the nitric oxide system, contributes to the etiology of diabetic nerve dysfunction.